Risk Factors and Treatment Outcome Analysis Associated with Second-Line Drug-Resistant Tuberculosis - Muralidhar Aaina; Kaliyaperumal Venkatesh; Brammacharry Usharani; Muthukumar Anbazhagi; Gerard Rakesh; Muthaiah Muthuraj (MDPI AG, 2021)
The present study aimed at analyzing the treatment outcomes and risk factors associated with fluoroquinolone drug resistance having mutations in the gyrA and gyrB genes. A total of 258 pulmonary tuberculosis samples with first-line drug-resistant (H, R, or HR) were subjected to GenoType MTBDRsl assay for the molecular detection of mutations. Among the 258 samples, 251 were drug-resistant tuberculosis and seven were sensitive to all first-line TB drugs. Out of 251 DR-TB cases, 42 cases were MDR TB, 200 were INH mono-resistant and nine cases were RIF mono-resistant tuberculosis. Out of 251 DR-TB cases performed with a MTBDRsl assay, 14 had Pre-XDR-FQ, one patient had pre-XDR-SLID, one had extensively drug-resistant tuberculosis (XDR-TB) and 235 cases were sensitive to both FQ and SLID drugs. The study group had a mean average of 42.7 ± 16.4 years. The overall successful treatment outcomes among the MDR, INH mono-resistant, and pre-XRD patients were 70.6%, 82.0%, and 51%, respectively. The percentage of risk for the unfavorable outcomes in the pre-XDR, INH -mono-resistant, and XDR cases were 113.84% increased risk with RR 2.14; 95% CI 0.7821-5.8468. The independent risk factor associated with the unfavorable outcomes to failure was 77.78% increased risk with RR 1.78; 95% CI 0.3375-9.3655. Logistic regression analysis revealed that the percentage relative risk among MDR-TB patients for gender, male (RR: 1.85), age ≥ 61 years (RR: 1.96), and diabetics (RR: 1.05) were 84.62%, 95.83%, and 4.76%, respectively. The independent risk factors associated with INH mono-resistant cases of age 16-60 (RR: 1.86), ≥61 year (RR: 1.18), and treated cases (RR: 5.06). This study presaged the significant risk of INH mono-resistant, pre-XDR, and MDR among males, young adults, diabetics, and patients with previous treatment failure. Timely identification of high-risk patients will give pronounced advantages to control drug resistance tuberculosis diseases.